2014
DOI: 10.1016/j.yexcr.2014.07.035
|View full text |Cite
|
Sign up to set email alerts
|

A syndecan-4 binding peptide derived from laminin 5 uses a novel PKCε pathway to induce cross-linked actin network (CLAN) formation in human trabecular meshwork (HTM) cells

Abstract: In this study, we examined the role(s) of syndecan-4 in regulating the formation of an actin geodesic dome structure called a cross-linked actin network (CLAN) in which syndecan-4 has previously been localized. CLANs have been described in several different cell types, but they have been most widely studied in human trabecular meshwork (HTM) cells where they may play a key role in controlling intraocular pressure by regulating aqueous humor outflow from the eye. In this study we show that a loss of cell surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…These findings are consistent with the morphological changes of basement membrane type extracellular matrix deposition in SIOH leading to SIG discussed above in the Morphology section. Proteins deposited include LAMA1 (laminin-1) (Dickerson et al, 1998), LAMA5 (laminin-5) (Filla et al, 2014) and COL4A1 (collagen type IV A1) (Zhou et al, 1998), as well as other extracellular matrix components including FN1 (fibronectin) (Steely et al, 1992; Zhou et al, 1998), TSP1 (thrombospondin-1) (Flugel-Koch et al, 2004), and ELN (elastin) (Yun et al, 1989). Glucocorticoid treatment further increases the resistance of glycosaminoglycans to enzymatic degradation (Johnson et al, 1990) and reduces hyaluronan synthesis (Engelbrecht-Schnur et al, 1997).…”
Section: Cell Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with the morphological changes of basement membrane type extracellular matrix deposition in SIOH leading to SIG discussed above in the Morphology section. Proteins deposited include LAMA1 (laminin-1) (Dickerson et al, 1998), LAMA5 (laminin-5) (Filla et al, 2014) and COL4A1 (collagen type IV A1) (Zhou et al, 1998), as well as other extracellular matrix components including FN1 (fibronectin) (Steely et al, 1992; Zhou et al, 1998), TSP1 (thrombospondin-1) (Flugel-Koch et al, 2004), and ELN (elastin) (Yun et al, 1989). Glucocorticoid treatment further increases the resistance of glycosaminoglycans to enzymatic degradation (Johnson et al, 1990) and reduces hyaluronan synthesis (Engelbrecht-Schnur et al, 1997).…”
Section: Cell Biologymentioning
confidence: 99%
“…These cross-linked actin networks contain a nidus of signaling proteins including SDC4 (syndecan-4), PIK3R1 (Phosphatidylinositol 3-kinase regulatory subunit α) and PDLIM1 at the regions where actin filaments intersect, suggesting that they are more than a structural component and may represent a signaling mechanism to sense changes in IOP. CLANs are regulated by interactions with the extracellular matrix through integrins especially the αvβ3 integrin (Filla et al, 2011; Filla et al, 2009; Filla et al, 2006), which is upregulated and activated by dexamethasone (Clark et al, 2013; Faralli et al, 2013) and syndecans (Filla et al, 2014) in cultured trabecular meshwork cells. This group showed that a number of integrin binding matrix proteins upregulated by glucocorticoid treatment of trabecular meshwork cells increase CLAN formation (Filla et al, 2006).…”
Section: Cell Biologymentioning
confidence: 99%
“…(Clark et al, 1994; Filla et al, 2011), dependent upon the cell surface laminin 5-derived syndecan-4 peptide. (Filla et al, 2014; Read et al, 2007). …”
Section: Similarities Between Lc and Jct Cells Related To Glaucomamentioning
confidence: 99%
“…Additional studies have demonstrated that DEX treatment plays a role in increased Cross-Linked Actin Network (CLAN) formation by increasing laminin-5 deposition within the ECM (Filla et al, 2014). Although the exact function of CLANs are unknown, they are found with increased frequency in the TM of glaucoma patients (Hoare et al, 2008).…”
Section: Changed Morphology/increased Depositions Within the Trabeculmentioning
confidence: 99%
“…Syndecans, which are a four-member family of transmembrane heparan sulfate proteoglycans (HSPG), contain extracellular domains that bind ECM proteins and other extracellular ligands. Novel studies show that laminin 5-derived PEP75, which binds to syndecan-4, activates a novel PKCε-signaling pathway that triggers CLAN formation (Filla et al, 2014). However, it is unknown whether these changes result in reorganization of the ECM that leads to increase outflow resistance or they are a stress response to increased IOP.…”
Section: Changed Morphology/increased Depositions Within the Trabeculmentioning
confidence: 99%